(untitled) (Journal of Educational Sciences, 2016)
The article presents the results of a study of undergraduates understanding University entity, role and peculiarities of formation and methods of competence development of knowledge extraction. In order to provide materials for use in other studies, the text presents widely authentic material, given the lengthy calculations of the essay. Observations show that the modern Kazakhstani undergraduates have many years’ experience of design knowledge and experience of extracting knowledge from yourself and others. But this experience is mostly not understood and used spontaneously, often stereotypical, spontaneously established habit. Therefore, in the context of teaching University disciplines University professors must conduct original alignment.